PREPARATION OF B-T-S SEMICONDUCTORS BY USING SOLID STATE REACTION AND STUDYING ITS STRUCTURAL AND PHYSICAL PROPERTIES - Ali Fuad Khairy; Khalid Hamdi Rzej; Abdul Hameed Mahdi Al-Saraf (Tikrit Journal of Pure Science)
In this study, the ceramic compound BaTi(1-x)SnxO3 was prepared at (x=0, 0.05, 0.1, 0.15, 0.2) and doped with SiO2 and Y2O3 for all concentrations by using solid state reaction at 1150 oC and sintering time of 6h. Structural properties were studied before and after adding SiO2 and Y2O3 by using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Energy dispersive X-ray (EDX). It is found that the compound BaTi(1-x)SnxO3 has tetragonal structure for all concentration except at (x=0.2) which has cubic structure. After adding SiO2 and Y2O3, the peaks height was increased especially at (110).